A New Paradigm for Edge Reconstruction in Fractional Quantum Hall States - Sabo, Ron; Gurman, Itamar; Rosenblatt, Amir; Lafont, Fabien; Banitt, Daniel; Park, Jinhong; Heiblum, Moty; Gefen, Yuval; Umansky, Vladimir; Mahalu, Diana (arXiv.org, 2016)
Questions on the nature of edge reconstruction and "where does the current flow" in the quantum Hall effect (QHE) have been debated for years. Moreover, the recent observation of proliferation of "upstream" neutral modes in the fractional QHE raised doubts about the present models of edge channels. In this article we focus on hole-conjugate states, nu=2/3 and nu=3/5, and present a new picture of their edge reconstruction. For example, while the present model for nu=2/3 consists of a single downstream charge channel with conductance 2/3 e^2/h and an upstream neutral mode, we show that the current is carried by two separate downstream edge channels, each with conductance 1/3 e^2/h, accompanied by upstream neutral mode(s). We find that if the two downstream channels are not equilibrated, inter-mode equilibration (via particle exchange) takes place over a distance of microns, with the two channels effectively behaving as a single channel. Moreover, the inter-channel equilibration is accompanied by an excitation of upstream neutral modes. In turn, the counter-propagating neutral modes, moving in close proximity to the charge modes, fragment into propagating charges, inducing thus downstream current fluctuations with zero net current - a novel mechanism for non-equilibrium noise. This unexpected edge reconstruction underlines the need for better understanding of edge reconstruction and energy transport in all fractional QHE states.